PENGARUH TEMPERATUR AIR CAMPURAN TERHADAP KUAT TEKAN BETON - Khairul Miswar (Portal: Jurnal Teknik Sipil, 2011)
This research is to know effect of variation of semen water and the temperature toward pressure strength of concrete with a few temperature level that is normal temperature (24oC), 50oC, 75oC, and 100oC. Cemen water factor ( FAS) used 0,45 and 0,55. Test object at this research is selinder of concrete of standard with diameter 15 cm and high 30 cm amount to the this 24 sample. This research evaluate the slump mortar and pressure strength the concrete. Result of examination show that degradation ratio assess the maximum slump for the FAS 0,45 and FAS 0,55 are 80,64 % and 90,33 %. It is happened when concrete mixture with the water temperature is 100oC. Result of research also show that concrete mixture with the normal temperature water (24oC) pressure strength maximum is 33,83 MPa for the FAS 0,45 and 20,80 MPa for the FAS 0,55.Key words: cemen water factor, pressure strength, temperature, degradation ratio, slump